허실 변증 설문지 개발 가능성에 대한 고찰 - 유현희(Hyun Hee Ryu); 이혜정(Hae Jung Lee); 장은수(Eun Su Jang); 이시우(Si Woo Lee); 이기상(Gi Sang Lee); 김종열(Jong Yeol Kim) (동의생리병리학회지, 2009)
Deficiency and excess pattern differentiation is unique characteristic of traditional oriental medicine on diagnosis and treatment. This differentiation is accomplished through pulse, tongue diagnosis and question examination, but most of these processes need to be objectified for efficacious treatment and traditional medicine development. In this study, we developed the deficiency and excess pattern questionnaire for objectification of question examination. The deficiency and excess pattern questionnaire was made out through The Traditional Oriental Medical Literature with Delphi Technique. Patients who visited oriental medical hospital filled out the questionnaire by themselves. Diagnosis of deficiency and excess pattern are conducted separately by oriental medical doctors with more than 5 years' clinical experience. Various physical condition factors were derived for the deficiency and excess pattern questionnaire. (Ordinary health degree, pain pattern, fatigue, weight change, sweating, uncomfortable awareness on chest and abdomen) Deficiency symptoms group acquired internal consistency, but excess symptoms group did not. (Cronbach's ${α}$ > 0.6) There were significant associations between doctor's diagnosis and deficiency and excess symptoms in 'ordinary heath degree', 'voice weakening', and 'chest distress' (p-value < 0.1) There were significant differences between deficiency and excess syndrome patients groups in deficiency questionnaire score but there were no significant differences between deficiency and excess syndrome patients groups in excess questionnaire score. We acquired the internal consistency and significant result of deficiency pattern questionnaire, but we can find out some difficulties in development of the excess pattern questionnaire. These difficulties are associated with insufficiency description of traditional literature and small number of patients diagnosed as excess pattern.